Surface Wrinkling Induced by Photofluidization of Low Molecular Azo Glasses. Issue 2 (13th December 2012) - Gruner, Philipp; Arlt, Michael; Fuhrmann‐Lieker, Thomas
Abstract Photoinduced surface wrinkling is demonstrated for a low molecular azo compound confined between a substrate and a thin inorganic elastic layer. The wrinkling process is investigated by time‐resolved light scattering as well as by two‐dimensional autocorrelation analysis of microscopic images. It is shown that the temporal evolution of the wrinkling pattern is directly controlled by the amount of photons absorbed by the sample and that there is no significant dependence of the equilibrium wavelength on irradiation intensity. Finally, the comparison of thermal and photoinduced wrinkling revealed that photoinduced wrinkles are characterized by a narrower mode distribution and less coarsening.